Feral cattle in the Chornobyl Biosphere Reserve: a combination of science and ethnoecology - Sergiy Zhyla (Theriologia Ukrainica)
In Ukraine, it is advisable to use a combination of science and the Polissian ethnoecology in landscape management and rewilding projects. The presence of feral cattle (Bos taurus, hereinafter referred to as cattle) in the Chornobyl Radiation and Ecological Biosphere Reserve (ChBR) requires a revision of the existing legislation and amendments to the Law of Ukraine On the Nature Reserve Fund of Ukraine to grant a conservation status to feral cattle. Nowadays, due to the legal ban on grazing livestock in nature reserves, feral cattle are outlawed. According to the experience of cattle farming in Polissia, grazing and controlled fires should complement each other. Insufficient intensity of ungulate grazing and the lack of a natural fire regime in the ChBZ have led to problems with the restoration of natural meadows and caused the massive spread of bushgrass (Calamagrostis epigejos). The war in the ChRB intensified the processes of further feralisation of Przewalski’s horse (Equus przewalskii) and feral cattle. The spatial distribution of the phytomass in cattle grazing areas is highly mosaic and on only young, early successional vegetation in the form of a green lawn may remain on the very fertile soil, whereas dry grass may be absent. Such green lawns in the ChBR cover a small percentage of the area, but they are important for reducing fire danger and creating biodiversity hotspots. For cattle are not able to hoof the snow, they are quite vulnerable to the formation of hard crusts on the snow cover, and at this time they can consume a significant amount of branchy fodder from raspberries (Rubus idaeus), apple trees (Malus domestica), lilacs (Syringa vulgaris) and other trees. Feeding on branch fodder by cattle can be an indicator of a lack of herbaceous fodder and starvation. Restoration of heathland (Calluna vulgaris) would improve winter grazing in the ChBR and increase the habitat capacity not only for cattle but also for other ungulates. In the area of the Polissia Nature Reserve, forest farms in the past had a clear division of grazing between winter grazing on heather and summer grazing on blue molinia (Molinia caerulea). However, due to the long absence of fires and cattle grazing, the cereal-heather heathland has been reforested and has turned into mainly green moss pine forests.